Risky Business: Consumer Attitudes, Perceptions, and Consumption Behaviors During COVID-19. Issue 2 (4th March 2022) - Taillon, Brian J.; Mai, Enping (Shirley); Haytko, Diana L.
Abstract: With consumers cautious of COVID-19, managers are forced to adapt to changes in consumer behavior, government regulations, and disrupted supply chains. Using Protection Motivation Theory, two studies investigate consumers' attitudes toward, and perceptions of, the disease to better understand consumer behaviors during a pandemic. Study 1, assessing young adults and their parents, shows students' attitudes, perceptions, and behaviors were riskier than their parents during the pandemic. Study 2 considers the influence of political affiliation, finding Democrats are more likely to take the threat seriously whereas Republicans were less likely to perceive COVID-19 as a threat; each modeled behavior that reflects their respective views. Practitioners must consider consumer's protection motivation and business risk levels when contemplating changes to business practice during this time.